CONFLICT AT SCHOOL: SCHOOL ENVIRONMENT AS A SPACE FOR EMBRACEMENT/MEDIATION AND TEACHER INTERVENTIONS IN THE LEARNING RELATIONSHIP - Souza, Jaqueline Saraiva de; Teixeira, Ana Paula; Silva, Jaqueline Moura da; Pessoa, Dayse Alves; Costa, Luciana Amaral de Mascena; Veras, Ana Lourdes Cruz; Coutinho, Diógenes José Gusmão (Revista Ibero-Americana de Humanidades, Ciências e Educação, 2023)
The present work arose from the report of several experiences lived by us as interns and even as teachers, such experiences made us reflect on the importance of the existence of a conflict mediator in the school context, considering that these conflicts will always exist, because where there is more than one thinking head there will be divergence of opinions. However, in the absence of the possibility of field research, the content was removed through bibliographic research, articles, books and scientific journals. As such, several opinions were found on how these conflicts arose; how the environment in which the student lives interferes as a cause; and like the school, the teacher or even the student himself can exercise his role as a mediator. The practice of group activities such as games or scavenger hunts was questioned in order to encourage social interaction, but it was still not enough. In view of this, we note that it is necessary to insert the curriculum of the educator, who may, in the future, assume other functions such as: supervisor, coordinator and even manager; the theme that both intrinsic and extrinsic conflicts will always exist and that not only academic training will be necessary, but also dynamics of living mainly with parents or guardians, and that such dynamics can be carried out through extra-curricular activities that manage to insert them and welcome them also at school. In this way, the school and the community will work together with the same objective as the formation of the student in a healthy and welcoming environment.